Emotional responses to virtual reality-based 3D spaces: focusing on ECG Response to single-person housing according to different plan configurations. Issue 5 (2nd September 2020) - Myung, Jeeyeon; Jun, Hanjong
ABSTRACT: The purpose of this study was to use Virtual Reality(VR) and electrocardiograms (ECGs) to analyse differences in autonomic nervous responses affected by the plan configuration. Four different plan configurations of single-person households were chosen based on a prior study and built using VR. An ECG was then recorded within each plan type and the average low-frequency/high-frequency (LF/HF) power ratio was calculated to measure the stress level in each space, and the results revealed significant differences among plan type(p < 0.05). These results provide compelling evidence that a plan configuration may affect the quality of space for single-person households and also suggest that choice of plan configuration appears to be effective in counteracting the stress that may exacerbate psychological disorders among single-person households.